Assessment of the Effect of Blood Glucose Levels on Standardized Uptake Value (SUV) and 18F-FDG Uptake at Tumors and Normal PET Examinations - Marwa Safa Riyadh; Samar Omran Issa (Iraqi Journal of Physics)
This study evaluated the relationship between the blood glucose level, maximal standardized uptake value (SUVmax), and 18F-FDG uptake in tissues at normal and tumour organs with positron emission tomography/computed tomography (PET/CT) examinations. On the morning of the procedure, finger-stick fasting blood glucose is routinely assessed. The study looked at the SUVmax in the liver and bone of 200 people with F-FDG PET/CT scans for tumors and healthy organs18. The study formed three groups of patients based on their serum glucose levels. The study retrospectively examined the relationship between glucose levels and standardized uptake values. The mean liver and bone SUVmax gradually decreased as blood glucose levels increased, starting at 160 mg/dl. All the groups whose blood glucose levels were between 100 and 160 mg/dl had a slight but significant increase in the uptake of 18F-fluorodeoxyglucose (FDG) in bones and livers compared to the group whose blood glucose levels were all normal. The study concludes that following a blood glucose level of 160 mg/dl, hyperglycemia progressively lowers the absorption of 18F-FDG by the liver and bones. Studies using FDG-PET are especially inaccurate when blood glucose levels are high. Therefore, individuals undergoing FDG-PET examinations should fast and consider their blood glucose levels.